Auditoria de repositórios arquivísticos digitais confiáveis: uma análise das normas ISO 14721 e ISO 16363 - Santos, Henrique Machado dos (2018)
This study aims to contextualize and discuss the applicability of OAIS - ISO 14721: 2012 and ACTDR - ISO 16363: 2012 standards in the context of trustworthy digital archival repositories. For this, the OAIS functional model is analyzed initially in the context of Archives, emphasizing the perspectives of preservation and guarantee of access to authentic documents in the long term. Subsequently, the ACTDR audit standard is analyzed by looking at its applicability to OAIS-compliant digital archival repositories. The methodology consists of a research of an applied nature, in which the data collection is carried out by means of records, which are planned through a database instrument. The data collection is based essentially on a documentary survey, contemplating norms and recommendations to which it composes the nucleus of this study. And in a complementary way, a bibliographic survey is used, consisting of previously published materials such as books, theses, dissertations and scientific articles retrieved by the Google Scholar search tool. The OAIS analysis demonstrates that there is theoretical compliance with Archival, although it is not explicit, it is possible to shape an archival repository based on its requirements. With this, an OAIS-compliant repository can contemplate principles such as provenance and uniqueness, as well as fit into the context of the seven archival functions. The OAIS functional model conceptualizes packet structures and information objects, which include fundamental properties for preservation, maintenance of authenticity and guarantee of access to digital documents. Therefore, OAIS is considered a prerequisite in the implementation of a trustworthy digital archival repository. In a second moment, the ACTDR audit pattern is analyzed to make explicit the potentially archival aspects that are implicit, so its detailing supports the auditing process of trustworthy digital archival repositories. The ACTDR standard is divided into three sections in which the requirements related to institutional policies of digital preservation, management of stored digital objects and the management of security and risk of the digital repository are subdivided. Among the contributions of this study, it is emphasized that the implementation of a trustworthy digital archival repository should initially consider the OAIS reference model, and, in a second moment, this repository should be audited by the ACTDR standard. In case the repository reaches the levels of reliability required in the audit, it is certified by the appropriate body. Finally, the complement of this study consists of the elaboration of a product, the "Manual for Auditing Reliable Digital Archival Repositories", thus establishing a dialogue between OAIS and ACTDR, in addition to considering archival aspects pertinent to long-term preservation. This manual synthesizes the knowledge discussed to serve as guidance to archivists working within digital archival repositories.